Правове регулювання дисциплінарного провадження - Коваленко, К. В.; Kovalenko, K. V.; ORCID: http://orcid.org/0000-0002-2105-9664; ResearcherID: J-7803-2016 (Вісник Харківського національного університету внутрішніх справ. - 2014. - № 4 (67). - С. 191-198, 2014)
Дисциплінарне провадження є формою реалізації дисциплінарної відповідальності, а неврегульованість цього питання на законодавчому рівні призводить до неправильного застосування норм права в області дисциплінарної відповідальності та, як наслідок, до порушення законності та прав працівників. На основі аналізу спеціальної літератури та наявних наукових розробок автором зроблено спробу прослідкувати становлення концепції дисциплінарного провадження, дати визначення дисциплінарного провадження в органах внутрішніх справ, виділити стадії дисциплінарного провадження, а також обставин, що виключають провадження у справі.

General legal principles, principles and features of the process of putting liability on police officers are disclosed. The essence of «disciplinary proceeding» is researched. On the basis of the analysis of leading scholars’ studies and regulatory acts in order to develop a single conceptual apparatus the author offers the definition of disciplinary proceedings and to classify disciplinary proceedings into certain stages. Principles of disciplinary proceeding are determined; their consistent implementation will make possible to achieve the goal of the process by the best way. Special attention is paid to the need of amending the Disciplinary Code of the Internal Affairs Agencies and fixing the definition of disciplinary proceeding, the exhaustive list of stages of disciplinary proceedings, and the list of circumstances precluding the possibility of disciplinary penalties. The relevance of the chosen issue is that the disciplinary liability of police officers is an important tool of guaranteeing discipline and ensuring compliance with the legislation by police officers. While this issue is unregulated at the legislative level it results to the incorrect implementation of law norms in the sphere of disciplinary liability and therefore a violation of law and the rights of police officers. The decision about the prosecution is an important event that may influence on the legal, moral, psychological and social state of a person. It affects human rights and freedoms, personal immunity and protection from abuse, honor and dignity of a person, his/her faith in justice and humanity of the law, professionalism of the state agencies that take all measures concerning legal liability, its validity in each case of prosecution. The disciplinary proceeding is a form of realizing disciplinary liability. The presence of collisions, gaps in the legal regulation in the sphere of disciplinary liability may be an obstacle to select only one correct measure of liability to an officer committed the disciplinary offense or lead to abuse and prosecution of innocent officers.

Дисциплинарное производство является формой реализации дисциплинарной ответственности, а неурегулированность данного вопроса на законодательном уровне приводит к неправильному применению норм права в области дисциплинарной ответственности и, как следствие, к нарушению законности и прав работников. На основе анализа специальной литературы и существующих научных разработок автором сделана попытка проследить становление концепции дисциплинарного производства, дать определение дисциплинарного производства в органах внутренних дел, выделить стадии дисциплинарного производства, а также обстоятельств, исключающих производство по делу.
Legal regulation of disciplinary proceedings
Правовое регулирование дисциплинарного производства
Коваленко, К. В. Правове регулювання дисциплінарного провадження / К. В. Коваленко // Вісник Харківського національного університету внутрішніх справ. - 2014. - № 4 (67). - С. 191-198.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; дисциплінарна відповідальність; дисциплінарне провадження; обставини, що виключають провадження у справі; discipline liability; disciplinary proceedings; stages of proceedings; circumstances precluding the proceedings; дисциплинарная ответственность; дисциплинарное производство; обстоятельства, исключающие производство по делу